Phytochemical of Ethanolic Extract of Cabbage (Brassica oleracea) Collected from Medan, Indonesia - Tarigan, Lela Diyana Br; Lister, I Nyoman Enrich; Fachrial, Edy; Armansyah, Adek (Talenta Publisher, 2022)
Phytochemical screening of ethanolic extract of cabbage (Brassica oleracea) has been successfully conducted. A phytochemical test was performed using FeCl3 to know the content of the phenolic compound from Cabbage. Cabbage is extracted until the ethanolic extract was obtained. It contained secondary metabolic compounds. mengandung senyawa metabolic sekunder. The largest secondary metabolic in cabbage extract was the flavonoid compound. The flavonoids total contained in the ethanolic extract of cabbage was 1.68 mg QE/g extract and the level of total phenol contained in the ethanolic extract was 45.090 mg GAE/g extract.